AKSELERASI PENGEMBANGAN WISATA HALAL BERBASIS BUDAYA DAN POTENSI DAERAH ACEH DENGAN PRINSIP MODERASI DAN PENGEMBANGAN UMKM - Nurkhalis (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
The halal tourism program created by Aceh Province is a regional advantage and uniqueness for developing tourism potential that is adapted to culture, religious values ​​and customs. However, the development of halal tourism does not yet have a concrete plan, has not been able to increase the participation of all stakeholders and is in accordance with the development of regional and cultural potential so that the number of tourists coming to Aceh Province is still concentrated in certain areas, for example Sabang, Banda Aceh and North Aceh, while In other areas, tourist visits have not been carried out optimally. Thus, the aim of this study is to develop a strategy to accelerate the development of halal tourism based on Aceh's regional and cultural potential with the principles of moderation and development of MSMEs. The methodology used in this study is to use a qualitative approach and SWOT analysis. The results of the study are 1) the strategy for developing halal tourism is carried out by maximizing strengths as internal potential to minimize the threat of failure to implement the halal tourism program in Aceh Province, 2) the implementation of the strategy in developing halal tourism is to analyze and manage tourism including planning, organizing, implementing and evaluating ; increase community participation; identify Aceh's potential by creating a grand design and promoting halal tourism both through conventional and online methods. Conclusion: The development of halal tourism requires synergy and commitment from all sectors, namely political, economic, social, technological, environmental and regulatory.